Le règlement des litiges commerciaux dans un système sans tribunaux de commerce : l'expérience québécoise - Lilkoff, Lubin (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
Quebec's Civil Code acknowledges the existence of a dual regime including both civil and commercial juridical operations. This distinction, which is derived from French Law, also exists in Belgian and German Law. These countries have created specialized commercial courts or tribunals with jurisdiction over commercial matters. They are staffed with judges drawn from business. One may ask how in fact a dualistic system of this nature functions in Quebec, given the absence of such special commercial tribunals. It may be noted that although there is no body of commercial law dealing exclusively with traders, there exists in fact a system of business law comprehensive enough to apply also to non-traders (Part I). In addition, the informal nature of the procedural rules, as well as the background of the judges who are selected mainly from the ranks of practising lawyers, permits one to discern a close resemblance between litigation before these courts and the conduct of trials before commercial tribunals (Part II).